The challenges of institutionalizing community-level social accountability mechanisms for health and nutrition: a qualitative study in Odisha, India - Francesca Feruglio; Nicholas Nisbett (BMC Health Services Research, 2018)
The primary research questions were ‘what kinds of community level mechanisms are functioning in randomly selected villages in 3 districts of state of Odisha' and 'how are they perceived to function by their members and frontline workers’.
Keywords: Community participation; Accountability